2013
DOI: 10.1128/aem.02251-12
|View full text |Cite
|
Sign up to set email alerts
|

Tetrathionate-Forming Thiosulfate Dehydrogenase from the Acidophilic, Chemolithoautotrophic Bacterium Acidithiobacillus ferrooxidans

Abstract: bThiosulfate dehydrogenase is known to play a significant role in thiosulfate oxidation in the acidophilic, obligately chemolithoautotroph, Acidithiobacillus ferrooxidans. Enzyme activity measured using ferricyanide as the electron acceptor was detected in cell extracts of A. ferrooxidans ATCC 23270 grown on tetrathionate or sulfur, but no activity was detected in ferrous iron-grown cells. The enzyme was enriched 63-fold from cell extracts of tetrathionate-grown cells. Maximum enzyme activity (13.8 U mg ؊1 ) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 52 publications
0
27
2
Order By: Relevance
“…6), which might reflect the paucity of available nitrogen (Siering et al, 2006). Numerous high-temperature, acidic habitats in Yellowstone National Park were shown to contain three novel lineages of nifH genes which appear to be active under the thermal, acidic conditions in these springs (Hamilton et al, 2011;Kikumoto et al, 2013); however, these nifH genes are distinct from those identified in our work. The GEOCHIP results presented here suggest that novel nif genes or nifH alleles function in nitrogen fixation under the low nutrient, low pH, and high temperature conditions in BSL.…”
Section: Biogeochemical Model Of Bsl Ecosystemcontrasting
confidence: 49%
“…6), which might reflect the paucity of available nitrogen (Siering et al, 2006). Numerous high-temperature, acidic habitats in Yellowstone National Park were shown to contain three novel lineages of nifH genes which appear to be active under the thermal, acidic conditions in these springs (Hamilton et al, 2011;Kikumoto et al, 2013); however, these nifH genes are distinct from those identified in our work. The GEOCHIP results presented here suggest that novel nif genes or nifH alleles function in nitrogen fixation under the low nutrient, low pH, and high temperature conditions in BSL.…”
Section: Biogeochemical Model Of Bsl Ecosystemcontrasting
confidence: 49%
“…TQO catalyzes the conversion of thiosulfate to tetrathionate, which is further used as a substrate for TetH; this results in the production of thiosulfate, sulfate, and sulfur atom (Table 3) (Yin et al, 2014a). The iron oxidizers A. ferrooxidans and A. ferrivorans also harbor a gene encoding thiosulfate dehydrogenase, a significant enzyme in thiosulfate oxidation (Kikumoto et al, 2013).…”
Section: Functionmentioning
confidence: 99%
“…As TetH is thought to be responsible for the hydrolysis of tetrathionate to thiosulfate, sulfur, and sulfate, the upregulation of doxD2 in the tetH overexpression strain and its downregulation in the ⌬tetH mutant according to qRT-PCR analysis indicated that the predicted doxD2 operon (5, 36) might play an important role in thiosulfate metabolism in A. ferrooxidans. This could be supported by the identification of the doxD2 cotranscribed gene AFE_0042, which encodes the thiosulfate dehydrogenase responsible for the enzymatic metabolism of thiosulfate (36). With regard to the two sqr genes, AFE_0267 seemed to play as important a role in sulfide oxidation as AFE_1792 according to qRT-PCR analysis, while only AFE_1792 was reported to be upregulated among sulfur-induced genes (5).…”
Section: Discussionmentioning
confidence: 89%
“…The study on oxidation of RISCs by A. ferrooxidans has proved particularly challenging, and the proposed models of sulfur metabolism were built based merely on the bioinformatic predictions of its genome sequence, coupled with analyses of its transcriptomic or proteomic experimental data (4,5). The functions of most genes involved in the oxidation of RISCs remain uncertain, though some genes have been characterized by cloning and expressing them in Escherichia coli (12,13,32,36). Considering the marked differences in the growth requirements between the genera Acidithiobacillus and Escherichia, the periplasmic or outer membrane proteins of A. ferrooxidans, such as some enzymes and electron carriers related to sulfur oxidation, might find it hard to function in E. coli.…”
Section: Discussionmentioning
confidence: 99%